2020
DOI: 10.3390/cells9071729
|View full text |Cite
|
Sign up to set email alerts
|

Daily Supplementation of L-Glutamine in Atrial Fibrillation Patients: The Effect on Heat Shock Proteins and Metabolites

Abstract: Pharmaco-therapeutic strategies of atrial fibrillation (AF) are moderately effective and do not prevent AF onset and progression. Therefore, there is an urgent need to develop novel therapies. Previous studies revealed heat shock protein (HSP)-inducing compounds to mitigate AF onset and progression. Such an HSP inducing compound is L-glutamine. In the current study we investigate the effect of L-glutamine supplementation on serum HSP27 and HSP70 levels and metabolite levels in patients with AF patients (n = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…Recent data showed for the first time the effect of L-glutamine on metabolites and serum HSP levels in patients with AF [130]. HSP27 and HSP70 were significantly decreased after 3 months of L-glutamine supplementation complemented by the normalization of metabolic pathways [130]. This knowledge may fuel future clinical studies on L-glutamine to improve cardiac function that may attenuate AF episodes.…”
Section: Nutraceuticals To Conserve Mitochondrial Functionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent data showed for the first time the effect of L-glutamine on metabolites and serum HSP levels in patients with AF [130]. HSP27 and HSP70 were significantly decreased after 3 months of L-glutamine supplementation complemented by the normalization of metabolic pathways [130]. This knowledge may fuel future clinical studies on L-glutamine to improve cardiac function that may attenuate AF episodes.…”
Section: Nutraceuticals To Conserve Mitochondrial Functionmentioning
confidence: 84%
“…The observed effect of L-glutamine on DNA damage, mitochondrial bioenergetics, and microtubule network reveals the importance of L-glutamine as a nutritional therapy for AF onset and progression. Recent data showed for the first time the effect of L-glutamine on metabolites and serum HSP levels in patients with AF [130]. HSP27 and HSP70 were significantly decreased after 3 months of L-glutamine supplementation complemented by the normalization of metabolic pathways [130].…”
Section: Nutraceuticals To Conserve Mitochondrial Functionmentioning
confidence: 99%
“…Further, a strong inverse correlation was observed between serum levels of HSPB1 or HSPA1A at baseline and after 3 months of L-glutamine supplementation. Interestingly, metabolites in the carbohydrate, nucleotide, and amino acid synthesis pathway were normalized in AF patients after 3 months of L-glutamine supplementation [ 55 ]. These findings indicate that L-glutamine supplementation affects HSP levels in AF patients and normalizes the metabolic pathways, which may attenuate proteostasis derailment and structural damage in cardiomyocytes in clinical AF.…”
Section: Pharmacological Boosting Of Hsr With Compoundsmentioning
confidence: 99%
“…As mentioned above, AF patients with high levels of HSPB1 at baseline and who were treated for 3 months with the HSP-inducing compound L-glutamine showed significant reduction in serum HSPB1 levels accompanied with normalization of metabolite levels compared with patients with low HSP levels at baseline. This all indicates that serum HSPB1 levels may guide patient-tailored therapy [ 55 ]. In addition, further research should elucidate whether the HSP levels in serum correlate with HSP levels in atrial tissue and the degree of electrical conduction abnormalities and voltage changes.…”
Section: Hsps As Biomarkers In Afmentioning
confidence: 99%
“…This discrepancy warrants further investigation on the exact role of aggregates on cardiomyocyte function. Starreveld studied whether the HSP-inducing compound L-glutamine has an effect on HSP levels in patients with atrial fibrillation [ 4 ]. Previous studies already revealed that HSP induction protects the heart against atrial fibrillation [ 5 , 6 ].…”
mentioning
confidence: 99%